Problem Based Learning in Medical Education: AQ2 AQ1 Handling Objections and Sustainable Implementation - William K., Lim (DOVE MEDICAL PRESS LTD, 2023)
The introduction of problem-based learning (PBL) in 1969 is considered the greatest innovation in medical education of the past 50 years. Since then, PBL has been implemented in different educational settings across virtually all health professions. However, some PBL schools gradually faced resistance from academic staff who were more familiar with traditional teacher-centred curricula. At times this has resulted in reversion to tradition or compromise whereby PBL is implemented within a lecture-based curriculum. Resistance can also emerge in a traditional school when a PBL curriculum is being considered for implementation. One of the first signs of this erosion is doubts 15 about PBL raised in the form of objections or criticisms. This perspective review describes eight objections raised to assert why PBL is inferior or untenable. The background to each objection is provided together with evidence-informed rebuttals derived from professional practice and the published literature. Best practices are discussed for sustainable management of a PBL-based curriculum. A well-implemented PBL curriculum with appropriate and cost-effective infrastructure, training, teaching-learning activities, and assessment will position schools to harness the full benefit of PBL in training medical and health professionals